The R2R3MYB Gene Family in Phyllostachys edulis: Genome-Wide Analysis and Identification of Stress or Development-Related R2R3MYBs - Hou, Dan; Cheng, Zhanchao; Xie, Lihua; Li, Xiangyu; Li, Juan; Mu, Shaohua; Gao, Jian (Frontiers in Plant Science, 2018)
The MYB transcription factor (TF) is one of the largest gene families in plants and involved to multiple biological processes. However, little is known about the MYB family and its functional role in the genome of moso bamboo. In the present study, a total of 114 R2R3MYB genes were first identified from moso bamboo genome and full-length non-chimeric (FLNC) reads. Phylogenetic analysis coupled with gene structure analysis and motif determination resulted in the division of these PheR2R3MYBs into 17 subgroups. The position of eight proteins along an external branch in the phylogenetic tree suggested their relatively ancient origin. The genes in this group were all substituted by (Met, M)/(Arg, R) at conservative W residues in both R2 and R3 repeats, and half were found to possess no transcriptional activation activity. The analysis of evolutionary patterns and divergence suggests that the expansion of PheMYBs was mainly attributable to whole genome duplication (WGD) under different selection pressures. Expressional analysis based on microarray and qRT-PCR data performed diverse expression patterns of R2R3MYBs in response to both various abiotic stimuli and flower development. Furthermore, the co-expression analysis of R2R3MYBs suggested an intricate interplay of growth- and stress-related responses. Finally, we found a hub gene, PheMYB4, was involved in a complex proteins interaction network. Further functional analysis indicated that ectopic overexpression of its homologous gene, PheMYB4-1, could increase tolerance to cold treatment and sensitivity to drought and salt treatment of transgenic Arabidopsis seedlings. These findings provide comprehensive insights into the MYB family members in moso bamboo and offer candidate MYB genes for further studies on their roles in stress resistance.